Storytelling on Screen An Online Playback Theatre Archive and Guidebook - Rosin, Jordan; Vogel, Heidi Winters; Lebron, Sammy (Open textbook library., 2021)
Playback Theatre is a form of community-centered storytelling theater where the audience tells stories, which are then reflected by a company of actors and musicians. Storytelling on Screen: An Online Playback Theatre Archive and Guidebook is an open education resource consisting of a collection of full-length recordings of online Playback Theatre performances, and a 55-page explanatory guidebook. The guidebook, featuring a foreword by Playback Theatre co-founder, Jo Salas, explains the adaptation to online performances and some of the key concepts, roles, and forms involved in online Playback Theatre. The resource as a whole is suitable for a wide range of theatre students in courses such as applied theatre, theatre for social justice, improvisation, theatre appreciation, or acting. The guidebook contains hyperlinks to specific sections of the archive where students can see a given form or concept in action, allowing for a comparison of how different companies approach a given form. If you are an artist, educator, or theatre-maker using this resource, please help us understand your use by filling out this form https://bit.ly/playback_interest